Online voucher sales system for the National Aptitude Test 2013 - Kapoor, Rohit, (SAGE Knowledge. Cases., 2016)
This case presents the real-life situation of a convener who has initiated the task of implementing an online voucher sales system to collect the fees from candidates for a National Aptitude Test. The IT application was to be developed by an external vendor, but a few days before the application's launch, the vendor's point of contact informed the convener that development had been delayed. This placed the convenor in a difficult situation because he had already announced the launch through the national media. The options available to him were rather few. He was faced with the dilemma of whether to announce the non-availability of online voucher system to the public and face the media trial or to explore the option of pushing the external vendor further to meet the deadline. The second option required him to coordinate with the senior management of the vendor company. In any case, the timelines were tight, and he had to make the decision promptly. It would be a difficult situation for the convener, in case the application failed.